Expansion and Hepatocytic Differentiation of Liver Progenitor Cells In Vivo Using a Vascularized Tissue Engineering Chamber in Mice - Forster, N.; Palmer, J.; Yeoh, G.; Ong, W.; Mitchell, G.; Slavin, J.; Tirnitz-Parker, Janina; Morrison, W. (Mary Ann Liebert, Inc. Publishers, 2011)
Current cell-based treatment alternatives to organ transplantation for liver failure remain unsatisfactory. Hepatocytes have a strong tendency to dedifferentiate and apoptose when isolated and maintained in culture. In contrast, liver progenitor cells (LPCs) are robust, easy to culture and have been shown to replace damaged hepatocytes in liver disease. In this study we investigate whether isolated LPCs can survive and differentiate toward mature hepatocytes in vivo when implanted into a heterotopic mouse tissue engineering chamber model. Healthy Balb/c mice and those put on a choline-deficient ethionin-supplemented diet to induce chronic liver disease were implanted with a tissue engineering chamber based on the epigastric flow through pedicle model, containing either 1 × 106 LPCs suspended in Matrigel, or LPC-spheroids produced by preculture for 1 week in Matrigel. Four weeks after implantation the chamber contents were harvested. In all four groups, progenitor cells persisted in large numbers to 4 weeks and demonstrated evidence of considerable proliferation judged by Ki67-positive cells. Periodic acid Schiff staining demonstrated differentiation of some cells into mature hepatocytes. Constructs grown from LPC-spheroids demonstrated considerably greater LPC survival than those from LPCs that were grown as monolayers and implanted as dissociated cells. The combined use of LPC spheroids and the vascularized chamber model could be the basis for a viable alternative to current treatments for chronic liver failure.